INTERACTION OF NANOSTRUCTURED LIPID CARRIERS WITH HUMAN MEIBUM - Niamprem, Pattravee; Milla, Thomas J.; Schuett, Burkhardt S.; Srinivas, S. P.; Tiyaboonchai, Waree (International Journal of Applied Pharmaceutics, 2019)
Objective: This study aimed to determine the possibility of nanostructured lipid carriers (NLCs) as a bionic tear film by determining the surface activities of the developed NLCs and their interaction with human meibomian lipid films. Methods: NLCs with different types of solid lipids and surfactants were prepared by a high-pressure homogenizer. The particle size was determined by dynamic light scattering. The surface activities of the NLCs and NLCs mixed with meibomian lipids were measured using a Langmuir trough and the resulting surface pressure area (Π-A) profiles were compared. These lipid films were further analyzed using fluorescence microscopy and scanning electron microscopy (SEM). Results: The particle size of prepared NLCs varied from 38–280 nm based on types of solid lipid and surfactant. All NLCs were highly surface active as indicated by their maximum surface pressure (Πmax). The Π-A profiles of meibum seeded with NLCs showed higher surface pressure than meibum alone and the shape of profiles were dominated by the meibomian lipids. These findings were in agreement with fluorescence and SEM micrographs, which revealed that the NLCs could adsorb and integrate to the meibomian lipid films as well as diffuse from the subphase to the lipid films. Conclusion: NLCs are surface active and can integrate with meibomian lipid films formed stable films. The type of interaction can be tailored by altering the solid lipids used in the formulation of the NLCs which could provide the means to develop efficient formulations for targeting dry eye disease related to a non-functional tear film lipid layer.